Debt relief and the rule of thumb: Analytical history of HIPC debt sustainability targets - Peter Hjertholm (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper traces the origins of HIPC debt sustainability targets. These targets are interpreted as `switching values', below which countries are expected to avoid debt service problems, but as such, they do not take into account that countries encounter debt problems for a variety of reasons and at different levels of debt. Most likely the `true' switching value of the debt-to-export ratio of many HIPCs lies below or above the present target. Regarding the `fiscal window', the lack of analytical basis for a 250 percent target for the debt-to-revenue ratio is noted, and the problems raised by the `openness-tax' condition are discussed. The paper concludes that sustainability targets, as presently applied, are not well supported in analytical terms.
Keywords: O11; F34; F35; 330; debt relief; debt sustainability targets; HIPC; switching values; Auslandsverschuldung; Schuldenerlass; Entwicklungsländer